PENGARUH CITRA PERUSAHAAN DAN KEPERCAYAAN NASABAH TERHADAP KEPUASAN NASABAH KOPERASI SIMPAN PINJAM UTAMA KARYA JEPARA - Achmad Arifin, 12.05.51.0134 (Students Journal of Economic and Management, 2016)
Their competition is very tight with the rise of each cooperative and the emergence of cooperative service products with different attributes, making customers choose to get the best services from the bank by giving satisfaction to customers. This study aimed to analyze the influence of corporate image and customer confidence in the customer satisfaction Karya Utama KSP Jepara. The population in this study is the work of Jepara Top KSP customers from January to December 2015 that bejumlah many as 267 customers. Based on the calculation Slovin obtained a sample of 73 respondents. The sampling technique used in this research is using purposive sampling method, the sampling based on certain criteria. The criteria set out in this sampling is customer Top KSP Jepara work for 2 years. Data analysis technique used is multiple linear regression. The results showed that the companys image a positive effect on customer satisfaction. The better the image of the company, customer satisfaction will increase. Customer confidence in a positive effect on customer satisfaction. The better the trust of customers, then customeer satisfaction will increase. Keywords: Corporate Image, Trust Customer and Customer Satisfaction.